Taxation of trusts: Quo Vadis? a discussion of changes to the taxation of trusts in the context of current law - Rensburg, A Van (Centre for Law and Society, 2026)
The aim of this dissertation is to discuss the general context of the taxation of trusts in South Africa, highlighting areas of uncertainties. The above is then viewed in the context of the recent changes to such taxation, in particular with regard to what have become known as 'business trusts'. Further, the proposals regarding the future taxation of capital gains in trusts, and the effectiveness of such taxes, are considered. The aim of the above is to arrive at a conclusion as to the question – are trusts still useful in the context of arranging one's affairs in a tax effective manner?